2019
DOI: 10.3390/pharmaceutics11070298
|View full text |Cite
|
Sign up to set email alerts
|

Delivery of Nanoparticles across the Intestinal Epithelium via the Transferrin Transport Pathway

Abstract: The aim of this study was to probe whether the transferrin (Tf) transport pathway can be exploited for intestinal delivery of nanoparticles. Tf was adsorbed on 100 nm model polystyrene nanoparticles (NP), followed by size characterisation of these systems. Cell uptake of Tf and Tf-adsorbed NP was investigated in intestinal epithelial Caco-2 cells cultured on multi-well plates and as differentiated polarised monolayers. Tf-NP demonstrated a remarkably higher cell uptake compared to unmodified NP in both non-pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 27 publications
0
22
1
Order By: Relevance
“…Interestingly, the uptake of both cow milk and intestinal epithelial cell EVs was notably higher in differentiated Caco-2 cells compared to undifferentiated cells, specifically 2-fold higher for milk EVs and 5-fold higher for cell-derived counterparts. Both milk and cell-derived EVs displayed notably higher levels of cell uptake than, for example, 100 nm unmodified polystyrene nanoparticles reported in our previous study [11]. Specifically, this difference amounts to 5% and 6.7% cell uptake for milk and cell EVs, respectively, versus 1.57% for polystyrene nanoparticles in undifferentiated cells, whereas in polarised monolayers cell uptake of milk and cell EVs was observed to be 13.31% and 31.83%, respectively, versus 4.1% with polystyrene nanoparticles.…”
Section: Discussioncontrasting
confidence: 46%
See 1 more Smart Citation
“…Interestingly, the uptake of both cow milk and intestinal epithelial cell EVs was notably higher in differentiated Caco-2 cells compared to undifferentiated cells, specifically 2-fold higher for milk EVs and 5-fold higher for cell-derived counterparts. Both milk and cell-derived EVs displayed notably higher levels of cell uptake than, for example, 100 nm unmodified polystyrene nanoparticles reported in our previous study [11]. Specifically, this difference amounts to 5% and 6.7% cell uptake for milk and cell EVs, respectively, versus 1.57% for polystyrene nanoparticles in undifferentiated cells, whereas in polarised monolayers cell uptake of milk and cell EVs was observed to be 13.31% and 31.83%, respectively, versus 4.1% with polystyrene nanoparticles.…”
Section: Discussioncontrasting
confidence: 46%
“…However, these systems tend to suffer from inefficient translocation across the highly effective and selective barrier of the intestinal mucosa, therefore requiring careful formulation. Drug nanocarrier systems utilised to improve oral drug bioavailability can be designed to target epithelial biological transport pathways [7,[9][10][11]. While some of these systems have shown potential in vitro and in animal studies, current understanding of orally-administered nanomedicine behaviours and biotransformation within the complex environment of the gastrointestinal tract (including interaction with gut biofluid and mucus, as well as potential toxicity) is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…The physicochemical characteristics of titania NPs, which might influence gastric toxicity, have been studied by many teams [ 136 , 137 , 138 , 139 ]. For example, it has been found that the properties of titania influence its entry pathway and further body penetration.…”
Section: Toxicity Of Titanium(iv) Oxidementioning
confidence: 99%
“…88 The Caco-2 model has been employed widely for the study or nanomedicines for oral delivery. 3, 89,90 However, the Caco-2 transwell system accounts for neither the constant uid ow nor the uid shear stress tolerated by epithelial cells in vivo, thereby skewing the predicted bioavailability of chemicals and/or nanomedicines. 91,92 Caco-2 cell monolayers additionally lack a mucus coating, which serves to (i) control the intestinal absorption of matter and (ii) shield the epithelium from harmful intraluminal contents in vivo.…”
Section: Gastrointestinal Models For the Study Of Nanoparticle Behaviourmentioning
confidence: 99%
“…91,92 Caco-2 cell monolayers additionally lack a mucus coating, which serves to (i) control the intestinal absorption of matter and (ii) shield the epithelium from harmful intraluminal contents in vivo. 89 Expanding on the latter, bile salts are considerably toxic (irritant) to epithelial cells despite being a major constituent of intestinal media. Thus, the potentially detrimental impact of SIF on the Caco-2 intestinal barrier model (which may otherwise be a useful strategy to model both the intestinal luminal uid and epithelium) may cause the overestimation of transepithelial permeation.…”
Section: Gastrointestinal Models For the Study Of Nanoparticle Behaviourmentioning
confidence: 99%